Involvement of proliferating cell nuclear antigen (cyclin) in DNA replication in living cells. - Zuber, M (1989)
Proliferating cell nuclear antigen (PCNA) (also called cyclin) is known to stimulate the activity of DNA polymerase delta but not the other DNA polymerases in vitro. We injected a human autoimmune antibody against PCNA into unfertilized eggs of Xenopus laevis and examined the effects of this antibody on the replication of injected plasmid DNA as well as egg chromosomes. The anti-PCNA antibody inhibited plasmid replication by up to 67%, demonstrating that PCNA is involved in plasmid replication in living cells. This result further implies that DNA polymerase delta is necessary for plasmid replication in vivo. Anti-PCNA antibody alone did not block plasmid replication completely, but the residual replication was abolished by coinjection of a monoclonal antibody against DNA polymerase alpha. Anti-DNA polymerase alpha alone inhibited plasmid replication by 63%. Thus, DNA polymerase alpha is also required for plasmid replication in this system. In similar studies on the replication of egg chromosomes, the inhibition by anti-PCNA antibody was only 30%, while anti-DNA polymerase alpha antibody blocked 73% of replication. We concluded that the replication machineries of chromosomes and plasmid differ in their relative content of DNA polymerase delta. In addition, we obtained evidence through the use of phenylbutyl deoxyguanosine, an inhibitor of DNA polymerase alpha, that the structure of DNA polymerase alpha holoenzyme for chromosome replication is significantly different from that for plasmid replication.